Statistics on Cannabis Users Skew Perceptions of Cannabis Use - Burns, Rachel M.; Caulkins, Jonathan P.; Everingham, Susan S.; Kilmer, Beau (Frontiers in Psychiatry, 2013)
Collecting information about the prevalence of cannabis use is necessary but not sufficient for understanding the size, dynamics, and outcomes associated with cannabis markets. This paper uses two data sets describing cannabis consumption in the United States and Europe to highlight 1) differences in inferences about sub-populations based on the measure used to quantify cannabis-related activity; 2) how different measures of cannabis-related activity can be used to more accurately describe trends in cannabis usage over time; and 3) the correlation between frequency of use in the past month and average grams consumed per day. Key findings: Focusing on days of use instead of prevalence shows substantially greater increases in U.S. cannabis use in recent years; however, the recent increase is mostly among adults, not youth. Relatively more rapid growth in use days also occurred among the college-educated and Hispanic. Further, data from a survey conducted in several European countries show a strong positive correlation between frequency of use and quantity consumed per day of use, suggesting consumption is even more skewed toward the minority of heavy users than is suggested by days-of-use calculations.